Kahoot Based Mufradat Learning Implementation for Non Specialist Teachers: Implementasi Pembelajaran Mufradat Berbasis Kahoot bagi Guru Non Spesialis - Azhar, Fairuz Azhar Hibatullah; Sauri, Sofyan; Khalid, Shofa Musthofa (Pedagogia : Jurnal Pendidikan, 2026)
General Background: The integration of digital media in early childhood education has become essential to support interactive and visual learning processes aligned with cognitive development stages. Specific Background: In Raudatul Atfal Fathul Ulum Garut, Arabic vocabulary learning is conducted by teachers without specialized linguistic backgrounds, requiring adaptive instructional strategies. Knowledge Gap: Previous studies largely emphasize media outcomes at higher education levels, leaving limited understanding of implementation mechanisms in early childhood contexts with non-specialist teachers. Aims: This study aims to describe the implementation stages of Kahoot-based mufradat learning, focusing on planning, execution, and evaluation processes. Results: Using a qualitative case study approach, findings reveal a structured transformation through three phases: planning via curated audio-visual content, implementation through gamified class orchestration that extends student attention, and evaluation using digital reports for objective cognitive monitoring. The use of Kahoot confirms multimedia learning theory by facilitating dual-channel processing that strengthens memory and sustains engagement. Novelty: The study highlights Kahoot as a pedagogical competence bridge that enables non-specialist teachers to deliver accurate and interactive Arabic vocabulary instruction. Implications: The findings suggest that gamification platforms can serve as strategic solutions for addressing teacher specialization gaps and support policy directions toward technology integration in early childhood education. Highlights• Structured three phase process ensures systematic instructional transformation• Gamified interaction prolongs student concentration beyond conventional duration• Digital reporting supports objective monitoring of cognitive development KeywordsKahoot; Mufradat Learning; Non Specialist Teachers; Early Childhood Education; Gamification